Presidential Address - Karnal bunt of wheat . A global perspective - D.V. SINGH - SINGH, D.V. (Indian Phytopathology, 2005)
First of all I wish to express my deep sense of gratitude to all the members of the Indian Phytopathological Society (IPS) for the honour they have conferred on me by electing as the President of the prestigious Society. It has been my pleasure and privilege to serve this Society for the last four decades. I would like to pay my tributes to all those who have nurtured the Society and brought it to International status and hope that the Society will continue to progress with greater thrust to serve the cause of the Plant Pathology. I have selected the subject, with which I was associated for more than 30 years of my active research period i.e. Karnal bunt of wheat.